Paleogeographic evolution and vertical motion of the central Lesser Antilles forearc since the Early Miocene: A potential driver for land fauna dispersals between the americas. (June 2023) - Cornée, Jean-Jacques; De Min, Lyvane; Lebrun, Jean-Frédéric; Quillévéré, Frédéric; Melinte-Dobrinescu, Mihaela; BouDagher-Fadel, Marcelle; Montheil, Lény; Marcaillou, Boris; Thinon, Isabelle; Philippon, Mélody
Abstract: Phylogenetic studies of present-day terrestrial organisms suggest that faunal dispersals between South America and the Greater Antilles may have occurred during the Cenozoic through the Lesser Antilles. However, because of the lack of geological data to unravel the areas that may have emerged along the Lesser Antilles trench, the migration paths used by their ancestors remain unknown. Here, we present novel paleogeographic maps of the central Lesser Antilles (extending from Guadeloupe to Martinique islands) which are built on the basis of onshore and offshore stratigraphic correlations (50 seismic lines, biostratigraphy of 9 dredged and 29 field samples, six sedimentary logs). We find that repetitive episodes of uplift and drowning have occurred in the central part of the Lesser Antilles during the Neogene. Offshore, the Marie-Galante Basin comprises three sedimentary megasequences that deposited between: (i) the Oligocene and Early Miocene, including the extinct arc, (ii) the Middle and Late Miocene and (iii) the latest Miocene and Holocene. These sediments infill a NNW-SEE trending forearc rift that opened during the Early Miocene. The megasequences are separated by subaerial regional unconformities that affect the rift shoulders. Onshore, we show that the lower part of the carbonate platform in Guadeloupe and La Désirade has deposited during the late Messinian. In Martinique, we refine the age of the carbonate deposits belonging to the extinct arc to the Chattian-Burdigalian, and evidence a major subaerial unconformity corresponding to the Middle Miocene. We propose that between Anguilla and Martinique, from north to south, large archipelagos, which are now drowned, have existed during the early Middle Miocene and the latest Miocene. We suggest that during the Miocene, the Lesser Antilles may have been used as a pathway for land-faunal dispersals from South America. Highlights: The Marie Galante Basin comprises three Eocene to present-day seismic megasequences. The Marie Galante Basin is an intra-arc rift with two Miocene uplifts. Martinique displays an early Middle Miocene uplift. ArChipelagos existed by the early Middle and latest Miocene in the Lesser Antilles. The Lesser Antilles can be a pathway for Cainozoic terrestrial fauna migrations.